Clinical and radiographic evaluation of maxillary central incisors exposure in patients undergoing maxillary advancement - Guilherme dos Santos Trento; Felipe Bueno Rosettti Bernabé; Delson João da Costa; Nelson Luis Barbosa Rebellato; Leandro Eduardo Klüppel; Rafaela Scariot (Dental Press Editora, 2015)
Abstract Introduction: Patients with dentofacial deformities may undergo orthodontic or orthodontic-surgical treatment. Both modalities can affect esthetics. Objective: This study aims to evaluate clinical and radiographic changes in exposure of maxillary central incisors occurring after orthognathic surgery for maxillary advancement. Methods: A total of 17 patients who underwent orthognathic surgery for maxillary advancement between September, 2010 and July, 2011 were selected. Exposure of maxillary central incisors was evaluated clinically and by lateral cephalograms. Measurements were taken one week before and three months after surgery. Data were paired in terms of sex, age, nasolabial angle, height and thickness of the upper lip, the amount of maxillary advancement, clinical exposure and inclination of maxillary central incisor by statistical tests (CI 95%). Results: After maxillary advancement, incisor clinical exposure had increased even with relaxed lips and under forced smile. Moreover, there was a mean increase of 23.33% revealed by lateral cephalograms. There was an inverse correlation between upper lip thickness and incisors postsurgical exposure revealed by radiographic images (p = 0.002). Conclusions: Significant changes in the exposure of maxillary central incisors occur after maxillary advancement, under the influence of some factors, especially lip thickness.